Strategi Pembina Ekstrakurikuler Lanbg Art dalam Meningkatkan Prestasi Musikalisasi Puisi di SMA Negeri 1 Lubuk Linggau - Muhammad Ezam Alparabi; Auzy Madona Adoma; Treny Hera (Lembag, 2024)
The formulation of the problem in the research is How is the implementation of learning the traditional Sedulang Setudung dance using audio visual media for students at SMP N 35 Palembang? The aim of this research is to find out how the traditional Sedulang Setudung dance lesson is implemented using audio-visual media for students at SMPN 35 Palembang. The method used in this research is a qualitative method. Data collection techniques in this research used observation, interviews and documentation. The data analysis techniques used in this research are 1. Data reduction, 2. Data presentation, 3. Drawing conclusions. Based on the research results, it can be concluded that: 1) At the planning stage the teacher plans learning based on the competencies that must be achieved in the form of a learning implementation plan. The learning planning steps at the meeting include preliminary activities, core activities and closing activities; 2) At the implementation stage, the teacher carries out traditional dance lessons in Sedulang Setudung groups in learning activities using direct learning strategies, and a learning approach that is centered on students as learning subjects. In the learning process and delivery of material the teacher uses audio visual media to facilitate students' understanding. The learning methods used in the strategy are demonstration methods and drill methods; 3) At the evaluation stage, the teacher conducts an evaluation in the form of a practical test which is carried out at the end of each learning activity. Based on the results of the study, it shows that students follow the traditional dance learning of Sedulang Setudung well. , and obtained excellent results of the final practical exam evaluation.